Consensus-based recommendations for the management of juvenile systemic sclerosis - Foeldvari, Ivan; Culpo, Roberta; Sperotto, Francesca; Anton, Jordi; Avcin, Tadej; Baildam, Eileen; Boros, Christina; Chaitow, Jeffrey; Constantin, Tamas; Kasapcopur, Ozgur; Knupp Feitosa De Oliveira, Sheila; Pilkington, Clarissa; et al. (Oxford University Press (OUP), 2021)
Juvenile systemic sclerosis (JSSc) is a rare disease of childhood and currently no international consensus exists with regard to its assessment and treatment. This SHARE (Single Hub and Access point for paediatric Rheumatology in Europe) initiative, based on expert opinion informed by the best available evidence, provides recommendations for the assessment and treatment of patients with JSSc with a view to improving their outcome. Experts focused attention not only on the skin assessment but also on the early signs of internal organ involvement whose proper treatment can significantly affect the long-term outcome. A score for disease severity is proposed in order to perform a structured assessment of outcome over time but a validation in a wider patient population is recommended. Finally, a stepwise treatment approach is proposed in order to unify the standard of care throughout Europe with the aim to reduce morbidity and mortality in this disease.
Keywords: assessment; juvenile systemic sclerosis; outcome; recommendations; scleroderma; severity score; treatment